2006
DOI: 10.1007/s10900-005-8188-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Parental Report of Blood Lead Testing In Children Enrolled in Medicaid with Medicaid Claims Data and Blood Lead Surveillance Reports

Abstract: The purposes of this study were to identify the congruence of blood lead testing based on parental self-reports with Medicaid claims and blood lead surveillance records, and to determine factors associated with agreement between parental reports of blood lead tests and Medicaid claims or blood lead surveillance records. Data were obtained from a cross-sectional mailed survey of a randomly selected sample of parents of children 1-2 years old enrolled in Medicaid (n=532) and from existing Medicaid claims and blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A study by Polivka et al suggested a greater likelihood of a child having BLL testing when the guardian was reminded through a letter, reminder card or phone call. 14,15 Patients seemed to prefer brochures or pamphlets. 15 Other factors that have improved BLL testing rates include receiving easy to read informational materials as well as videos with lead poisoning education.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study by Polivka et al suggested a greater likelihood of a child having BLL testing when the guardian was reminded through a letter, reminder card or phone call. 14,15 Patients seemed to prefer brochures or pamphlets. 15 Other factors that have improved BLL testing rates include receiving easy to read informational materials as well as videos with lead poisoning education.…”
Section: Discussionmentioning
confidence: 99%
“…15 Other factors that have improved BLL testing rates include receiving easy to read informational materials as well as videos with lead poisoning education. [14][15][16] Focus groups that looked at barriers to BLL testing showed that parents preferred to have all of their testing performed at the same facility and did not like to travel to multiple locations to have testing performed. 16 These parents also stated that they were hesitant to have testing done due to the traumatizing nature of multiple blood tests and immunizations for children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parents do not always know whether their child had a blood lead test. 33 Second, because of the small sample size of the study, the generalizability of the results is limited. Third, the age cutoffs for a blood lead test in the HCPS and UDS are different from CDC data.…”
Section: Implications For Policy and Practicementioning
confidence: 99%